Identifying and exploring the favorable factors that help to slow the progression of disease in patients with mild cervical spondylotic myelopathy - Taotao Lin; Zhipeng Yao; Zhehao Xiao; Rongcan Wu; Yujie Zhao; Dehui Chen; Linquan Zhou; Zhenyu Wang; Wenge Liu (Scientific Reports, 2024)
Abstract To explore the favorable factors that help slow the progression of disease in patients with mild Cervical Spondylotic Myelopathy (CSM). A retrospective analysis was conducted, involving the enrollment of 115 CSM patients. The categorization of patients into two groups was based on the duration of symptoms, assessments using the mJOA scale and Health Transition (HT) scores: mild-slow group and severe-rapid group. We found that the patients in both groups had similar degrees of spinal cord compression, but mild-slow group were older and had smaller C2–C7 cobb angle (Flexion) (CL(F)), C2–C7 cobb angle (Range of motion) (CL(ROM)), Transverse area (TA), Normal-TA, Compressive spinal canal area (CSCA), Normal-Spinal canal area (Normal-SCA) and lower Spinal cord increased signal intensity (ISI) Grade than the severe-rapid group. A binary logistic regression analysis showed that CL(ROM) and Normal-TA are favorable factors to help slow the progression of disease patients with mild CSM. Through ROC curves, we found that when CL(ROM) < 39.1° and Normal-TA < 80.5mm2, the progression of disease in CSM patients may be slower. Meanwhile, we obtained a prediction formula by introducing joint prediction factor: L = CL(ROM) + 2.175 * Normal-TA. And found that when L < 213.0, the disease progression of patients may be slower which was superior to calculate CL(ROM) and Normal-TA separately.